Associations of long-term hyperoxemia, survival, and neurological outcomes in extracorporeal cardiopulmonary resuscitation patients undergoing targeted temperature management: A retrospective observational analysis of the SAVE-J Ⅱ study - Tomoaki Takeda; Hayato Taniguchi; Hiroshi Honzawa; Takeru Abe; Ichiro Takeuchi; Akihiko Inoue; Toru Hifumi; Tetsuya Sakamoto; Yasuhiro Kuroda (Resuscitation Plus)
Background: Extracorporeal cardiopulmonary resuscitation (ECPR) can improve survival rates and neurological outcomes of patients with out-of-hospital cardiac arrest (OHCA). High levels of partial pressure of arterial oxygen (PaO2) negatively affect survival and neurological outcomes in patients with OHCA. However, research on associations of hyperoxemia with survival and neurological outcomes after ECPR remains limited, especially considering targeted temperature management (TTM) administration to patients. Additionally, few reports have examined the impact of hyperoxemia beyond 24 h. In this study, we aimed to examine the effect of prolonged hyperoxemia on survival and neurological outcomes after ECPR for OHCA in patients undergoing TTM. Methods: We performed a secondary observational analysis of data from the SAVE-J Ⅱ study, a retrospective, multicenter registry study of ECPR of patients with OHCA. Data on arterial PaO2 after ECPR for intensive care unit days 2–4 were collected and averaged. Patients were divided into two groups: hyperoxic (PaO2 ≥ 300 mmHg) and non-hyperoxic (PaO2 < 300 mmHg). Each variable was compared between the groups. Additionally, survival and mortality rates at discharge were compared, and factors associated with survival (primary outcome) and neurological outcomes (secondary outcome) at discharge were examined. Results: The multivariate analysis for survival at discharge showed that age, initial ventricular fibrillation/ventricular tachycardia (VF/VT) waveform, P = 0.0004), and hyperoxemia were significant factors. For neurological outcomes at discharge, significant factors included age, initial VF/VT waveform, hemoglobin level at presentation, and hyperoxemia. Conclusions: Prolonged hyperoxemia was significantly associated with worse survival and neurological outcomes after ECPR for OHCA in patients who underwent TTM.